Does declining income caused by the COVID-19 pandemic affect Chinese individuals’ future risky decision-making and intertemporal choices? A construal level perspective - Hua, Yifei; Mi, Jiaxin (Frontiers in Psychology, 2025)
In order to evaluate how residents choose savings and consumption behavior within the context of the income changes, which resulted from the COVID-19 pandemic, this paper constructed a conditional process model to study the impact of residents’ declining income on their low risk savings behavior and advanced consumption behavior from a cognitive perspective. We found that residents with declining income preferred low risk savings and advanced consumption behavior; residents with lower incomes, whose original income was higher, were more likely to be influenced by anxiety about perceived emergency supply shortages. The moderating role of social trust emerged only after supply shortage anxiety mediated the effect, and this moderation differed significantly based on construal level. This paper explored the impact of declining income and the emotional fluctuations that resulted from the COVID-19 epidemic on the differential choice of residents’ savings and consumption behavior. It can provide microeconomic guidance for similar emergencies in the future.